Targeted Disruption of Toxoplasma gondii Serine Protease Inhibitor 1 Increases Bradyzoite Cyst Formation In Vitro and Parasite Tissue Burden in Mice - Pszenny, Viviana (American Society for Microbiology, 2012)
As an intracellular protozoan parasite, Toxoplasma gondii is likely to exploit proteases for host cell invasion, acquisition of nutrients, avoidance of host protective responses, escape from the parasitophorous vacuole, differentiation, and other activities. T. gondii serine protease inhibitor 1 (TgPI1) is the most abundantly expressed protease inhibitor in parasite tachyzoites. We show here that alternative splicing produces two TgPI1 isoforms, both of which are secreted via dense granules into the parasitophorous vacuole shortly after invasion, become progressively more abundant over the course of the infectious cycle, and can be detected in the infected host cell cytoplasm. To investigate TgPI1 function, the endogenous genomic locus was disrupted in the RH strain background. ΔTgPI1 parasites replicate normally as tachyzoites but exhibit increased bradyzoite gene transcription and labeling of vacuoles with Dolichos biflorus lectin under conditions promoting in vitro differentiation. The differentiation phenotype can be partially complemented by either TgPI1 isoform. Mice infected with the ΔTgPI1 mutant display ∼3-fold-increased parasite burden in the spleen and liver, and this in vivo phenotype is also complemented by either TgPI1 isoform. These results demonstrate that TgPI1 influences both parasite virulence and bradyzoite differentiation, presumably by inhibiting parasite and/or host serine proteases.